Efektivitas Penggunaan Media Wordwall untuk Meningkatkan Minat Belajar Siswa Kelas VII SMPN 1 Cipicung - Ramanda, Rio; Gustiana, Eva (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to increase the effectiveness of woodwall media on the learning interest of SMPN 1 Cipicung students. The method used in this study uses a quantitative approach with pre-experimental designs (non-designs) in the form of intact-group comparison). The instruments used are observation, interviews, and questionnaires. The research data obtained from the data of the results of the questionnaire that was declared valid using the instrument test, namely the validity and reliability test. Data analysis techniques used normality tests, homogeneity tests, and t-tests. The results of data analysis show that ICT learning using wordwall media has been effectively applied to increase the learning interest of grade VII students of SMPN 1 Cipicung. In the delivery of learning materials, it shows the effect of direct involvement between teachers and students so that it can facilitate the teaching and learning process so that the expected goals can be achieved, especially in increasing students' interest in learning.